Pengaruh E-Trust, Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian pada E-Commerce Tokopedia pada Generasi Z di Kota Bengkulu - Julita Nesti Amanda; M.Noor Armi; Veny Puspita (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this study was to determine the effect of e-trust, online customer reviews, and online customer ratings on purchasing decisions on E-commerce Tokopedia for generation Z in Bengkulu City. The population in this study are consumers who have bought products in the Tokopedia e-commerce in generation Z in Bengkulu City and the number of respondents is 110 respondents. This research method is (explanatory research). Sampling in this study was carried out using non-probability sampling techniques. In this study, data collection was obtained from a questionnaire with Google Form media which would be distributed online and offline. The results of the first hypothesis research show that e-trust (X1) has a significant effect on purchasing decisions (Y) Tokopedia for Generation Z in Bengkulu City, the results of the second hypothesis research show that online customer review (X2) has no effect on purchasing decisions (Y) Tokopedia for Generation Z in Bengkulu City, the results of the third hypothesis show that online customer rating (X3) affects purchasing decisions (Y) Tokopedia for Generation Z in Bengkulu City, the results of the fourth hypothesis show that e-trust, online customer rating, online customer review simultaneously affect Tokopedia purchasing decisions for Generation Z in Bengkulu City.